Online Monitoring Oxidative Products and Metabolites of Nicotine by Free Radicals Generation with Fenton Reaction in Tandem Mass Spectrometry - Shih-Shin Liang; Yow-Ling Shiue; Chao-Jen Kuo; Su-Er Guo; Wei-Ting Liao; Eing-Mei Tsai (The Scientific World Journal)
In general, over 70% absorbed nicotine is metabolized to cotinine and trans-3′-hydroxycotinine by cytochrome oxidase P450, and nicotine is also a major addictive and the psychoactive component in cigarettes. As a xenobiotic metabolism, hydrophobic compounds are usually converted into more hydrophilic products through enzyme systems such as cytochrome oxidase P450, sulfotransferases, and UDP-glucuronosyltransferases to deliver drug metabolites out of the cell during the drug metabolic process. In this study, an electrodeless electrochemical oxidation (EEO) reaction via Fenton reaction by producing free radical to react with nicotine to immediately monitor the oxidative products and metabolic derivatives of nicotine by tandem mass spectrometer (MS) is done. Fenton reaction generates free radicals via ferrous ion (Fe2+) and hydrogen peroxide (H2O2) to oxidize DNA and to degrade proteins in cells. In the EEO method, the oxidative products of nicotine including cotinine, cotinine-N-oxide, trans-3′-hydroxycotinine, nornicotine, norcotinine, 4-oxo-4-(3-pyridyl)-butanoic acid, 4-hydroxy-4-(3-pyridyl)-butanoic acid, and nicotine-N′-oxide were detected by tandem mass spectrometer to simulate the changes of nicotine and its derivatives in a time-dependent manner.